2012
DOI: 10.3329/bjpt.v19i2.13134
|View full text |Cite
|
Sign up to set email alerts
|

Pollen morphology of <i>Begonia</i> L. (Begoniaceae) in Nepal

Abstract: The pollen morphology of 28 Begonia species of Nepal has been examined by scanning electron microscopy (SEM). Comparative pollen analysis was made based on size, shape in polar and equatorial views, P/E ratio, aperture, and exine ornamentation. In this study, four types of pollen ornamentation morphology have been identified. Among Nepalese Begonia, B. roxburghii (section Sphenanthera) has the smallest pollen (11.2-12.8 × 6.4-7.0 µm) and B. flagellaris (section Diploclinium) has the largest pollen (24.3-30.6 ×… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Based on our observation, all pollen grain of six Begonia species showed that the proximal and distal faces of the axine are alike (isopolar) and has three compound apertures (three zonocolporate). [19].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on our observation, all pollen grain of six Begonia species showed that the proximal and distal faces of the axine are alike (isopolar) and has three compound apertures (three zonocolporate). [19].…”
Section: Resultsmentioning
confidence: 99%
“…Determination of the shape of pollen can be determined by comparing the length of the polar axis with the equatorial axis. The size of the pollen is determined followed van den Berg [21] and Rajbhandary et al [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pollen identification was conducted according to the identification book (Hesse et al 2009;Halbritter et al 2018); and Palynological Database (www.paldat.org). The measurements were conducted for polar (P) diameter and equatorial (E) diameter (Rajbhandary et al 2012). Classification of the pollen types followed the formula from Halbritter et al (2018), which considered the ratio between polar axis length and equatorial diameter.…”
Section: Pollen Preparation and Measurementmentioning
confidence: 99%
“…Therefore, study of different characteristics would help in resolving the relationships and delimitation of these species. Pollen morphology is proved to be a useful character for improving the accuracy in the identification and classification of several plant groups (Erdtman, 1952;Rajbhandary et al, 2012;Özler et al, 2013;Sawar and Takahashi, 2013). Despite pollen morphology of Verbascum species was studied by several authors (Erdtman, 1952;Filippini et al, 1990;Perveen, 1993;Lobin and Pormbski, 1994;Bukhari and Alfarhan, 2006;Kheiri et al, 2006;Pehlivan et al, 2008), the pollens of Verbascum found in Iraq has never been investigated.…”
Section: Introductionmentioning
confidence: 99%